Battle for the Falklands / Max Hastings and Simon Jenkins. - Hastings, Max.; Jenkins, Simon (London : M. Joseph, 1983)
The Falkland Islands war was characterized by an extraordinary blend of drama and tragi-comedy. It began with an incident so bizarre that few could take it seriously: the arrival of Argentinian scrap merchants on one of the earth's most godforsaken spots. Two months later a thousand men had died, and the islands had seen the biggest air/sea battle since the Second World War.
Includes index.
Map on lining papers.
Keywords: 1982; Falkland Islands War, 1982.; Guerre des Malouines, 1982.